Pengolahan Keanekaragaman Pangan Non Beras Berbasis Sumber Daya Lokal Guna Membentuk Ketahanan Pangan di Desa Tosari Pasuruan - Arofatul Muawanah; Laila, Itsna Noor (CV Putra Publisher, 2024)
Food security is one of the government's development agendas to maintain the country's food stability. Utilisation of local commodities is one of the efforts to establish food security. This will reduce people's dependence on rice consumption. Simultaneous efforts by introducing the potential of local commodities as staple food is one that can be done in Tosari Village, Tosari District, Pasuruan Regency. The purpose of this research is to build the food security of the Tosari Village community through food processing empowerment activities based on my local resources. Using the Participatory Action Research method, community empowerment activities were carried out through the theme of processing the diversity of non-rice food consumption based on local resources. This activity is in partnership with the Department of Agriculture and Food Security of Pasuruan Regency, East Java. The results show that the people of Tosari Village are very enthusiastic about participating in this activity, this activity opens insights for them regarding the nutritional content of local commodities that are equivalent to rice and can utilise them into processed products that have selling value